MENINGKATKAN INTERAKSI DAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN GOOGLE CLASSROOM UNTUK KELAS DARING BIOLOGI DI SMA - SUGENG HARIYADI (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2021)
This action research was to increase the student interaction in the learning process. The subjects were the students at class X MIPA 4 SMA Negeri 1 Tarakan, consisting of 35 students (18 male and 17 female). It was held in the odd semester of the 2020-2021. The treatment given was by introducing the use of Google Classroom as the platfom of the learning. The result shows that there was an increase of the student interaction in the learning process on the Protista subject matter, by looking at the interactive score, namely the difference between the final score and the previous score > 30 with a score of 25, from 5.7% in cycle I to 0.0%, indicating an increase in student interactive, it even occurs interactively for all students in the learning process in cycle II, and this has a significant effect on student learning outcomes. Student learning outcomes increased from 76.2% in cycle I to 78.1% in cycle II, with attendance of students in cycle I of 99.0% and cycle II of 96.2%. There was an increase in student interaction in the learning and completeness of 80.0% with an average value of 65.9. It can be concluded that learning using Google Classroom